The Xanthomonas campestris effector protein XopDXcc8004 triggers plant disease tolerance by targeting DELLA proteins. Issue 3 (9th July 2014) - Tan, Leitao; Rong, Wei; Luo, Hongli; Chen, Yinhua; He, Chaozu
Summary: Plants protect themselves from the harmful effects of pathogens by resistance and tolerance. Disease resistance, which eliminates pathogens, can be modulated by bacterial type III effectors. Little is known about whether disease tolerance, which sustains host fitness with a given pathogen burden, is regulated by effectors. Here, we examined the effects of the Xanthomonas effector protein XopD Xcc 8004 on plant disease defenses by constructing knockout and complemented Xanthomonas strains, and performing inoculation studies in radish ( Raphanus sativus L. var. radiculus XiaoJinZhong) and Arabidopsis plants. XopD Xcc 8004 suppresses disease symptoms without changing bacterial titers in infected leaves. In Arabidopsis, XopD Xcc 8004 delays the hormone gibberellin (GA)‐mediated degradation of RGA (repressor of ga1‐3), one of five DELLA proteins that repress GA signaling and promote plant tolerance under biotic and abiotic stresses. The ERF‐associated amphiphilic repression (EAR) motif‐containing region of XopD Xcc 8004 interacts with the DELLA domain of RGA and might interfere with the GA‐induced binding of GID1, a GA receptor, to RGA. The EAR motif was found to be present in a number of plant transcriptional regulators. Thus, our data suggest that bacterial pathogens might have evolved effectors, which probably mimic host components, to initiate disease tolerance and enhance their survival.